2004
DOI: 10.1111/j.1365-2044.2004.03707.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative complications during percutaneous tracheostomy in obese patients

Abstract: SummaryThe safety of percutaneous tracheostomy in 73 obese patients (body mass index ‡ 27.5 kg.m )2 ) in a cohort of 474 adults was studied. Four percutaneous techniques were employed (percutaneous dilational tracheostomy, n = 48; Ciaglia Blue Rhino, n = 157; guide wire dilating forceps, n = 62, translaryngeal tracheostomy, n = 207). The overall complication rate was 43.8% (n = 32) in the obese group compared to 18.2% (n = 73) in the control group (p < 0.001). Seven (9.6%) obese patients suffered life-threaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 22 publications
2
93
0
5
Order By: Relevance
“…The overall complication rate was 43.8% in the obese group compared to 18.2% in the control group (P<0.001) and obesity was associated with 4.9-fold increased risk for serious complications (18 …”
Section: Obesitymentioning
confidence: 97%
“…The overall complication rate was 43.8% in the obese group compared to 18.2% in the control group (P<0.001) and obesity was associated with 4.9-fold increased risk for serious complications (18 …”
Section: Obesitymentioning
confidence: 97%
“…A number of small retrospective studies documented no difference in complication rates with the PDT procedure in obese patients. [84][85][86][87][88] The largest study examining this issue reported a singlecenter prospective analysis of 1,000 PDT procedures (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) in ICU subjects with increased bleeding risk or obesity. 89 They identified that increased international normalized ratio was the most important risk factor for bleeding (OR 2.99, 95% CI 1.26 -7.08), followed by thrombocytopenia with platelet count Ͻ 100,000 cells/L (OR 1.99, 95% CI 0.99 -3.95).…”
Section: High-risk Patients and Percutaneous Dilatational Tracheostomymentioning
confidence: 99%
“…En esta serie de casos, el IMC resultó significativo para la presentación de complicaciones, lo cual coincide con lo reportado por otros autores, quienes han referido un riesgo significativamente mayor en los pacientes obesos (23)(24)(25) , sobre todo en el período intraoperatorio y postoperatorio temprano, especialmente en los que cuentan con un IMC igual o superior a 35 (26,27) . Además de los mencionados, los pacientes con intubación orotraqueal prolongada tuvieron mayor riesgo de resultados adversos, lo cual ha sido señalado por otros autores, quienes reportaron 1.42 veces más probabilidad de tener una complicación postoperatoria tardía en individuos intubados por más de una semana; por su parte, la relación que se distinguió en este estudio entre resultados adversos y el tipo de anestesia empleado, difiere de los hallazgos en otras investigaciones, donde no se identificaron diferencias (13) .…”
Section: Discussionunclassified